Burhoe's Legacy: Lessons for Europeans - Drees, Willem B. (Zygon, 1998)
Ralph Burhoe's ideas have not been well received in European Protestant theology. His approach has been at odds with the dominant resistance to natural theology on the Continent, and it has not fit well with reconciling attempts from the United Kingdom either. However, Burhoe's interest in the role of religions in the emergence of human nature and culture, including the interest in noncognitive functions of religion, should be taken to heart. Besides, he has set an example for Europeans with respect to method in dealing with first-rate science.